PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP PRESTASI BELAJAR IPA DITINJAU DARI KEAKTIFAN SISWA - Retno Utaminingsih; Dyan Asih Pratiwi (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2019)
This research aims to determine the influence of ‘think pair share’ cooperative learning model on Science learning achievement as viewed from students’ activeness. This research was conducted at Selang State Elementary School, Gunung Kidul regency, academic year 2018/2019 with a population that consists of 2 classes of odd semester fourth graders, totaling 46 students. The research type is quasi experiment, students from IV-A and IV-B classes were taken as research samples. The data collection techniques used were documentation technique; test technique, and questionnaires. Test item validity was calculated using a product moment correlation formula. Test item reliability was calculated using the KR-20 formula and the questionnaire instrument using Cronbach’s alpha. The data analysis technique used was ancova test after applying requirement analysis tests which included distribution normality test, variant homogeneity test, and correlation linearity test. The research results descriptively showed that the tendency of Science learning achievement where ‘think-pair-share’ learning model was used had an average of 22.217 (very high); and the tendency of students’ learning activeness had an average of 69.78 (very high). The tendency of Science learning achievement in which expository learning model was used had an average of 18.83 (high), and the tendency of students’ learning activeness had an average of 57.609 (medium). Comparatively there was a very significant difference in students’ Science learning achievements between Selang State Elementary School Gunung Kidul fourth graders who used ‘think-pair-share’ model and those who used expository model in terms of students’ activeness (Fcount = 0.075 with p = 0.781). The average of students’ Science learning achievement scores and students’ activeness in those who used the ‘think-pair-share’ learning model are higher than those who used the expository learning model.